Deficiencia en el manejo informático y su aporte en la organización del archivo digital - Granados Vera, Adrian Moises (2020)
The present case study tries to make known the consequences of the absence of computer management in the administrative management of the department of human talent; the objective of this research is to analyze what would be the results of the lack of knowledge of the secretaries of the administrative area. This is a descriptive type investigation, in the fact that we are going to describe the causes that would cause the lack of knowledge in the computing field for today's secretaries, where we apply the inductive method and the survey technique in which we develop a questionnaire necessary for the collection of data that will be used to conclude this case study. The results obtained through the process tell us that having adequate knowledge in computer science facilitates things for a secretary despite this many collaborators do not have the due knowledge to exercise the position. The conclusions that you can reach with this is to advise and train the secretary of all the areas arranged by the company in order to have the ideal approach that facilitates the help of the digital archive in administrative processes giving better results in the Autonomous Municipal Decentralized Government of the Canton "Baba".